Cytokine Release Syndrome Induced by Pembrolizumab for Metastatic Anal Melanoma - Erica Martel; Shijia Li; Mayssaa Hoteit; Zubin Bham (Case Reports in Hematology)
Cytokine release syndrome (CRS) is a rare systemic inflammatory response that can be triggered by certain drugs and infections, commonly diagnosed at a disseminated stage, leading to poor prognosis. This has been well described following chimeric antigen receptor T-cell (CAR-T) therapy but has rarely been reported following antiprogrammed death ligand-1 (PDL-1) therapy. We present the case of an 86-year-old male with metastatic anal melanoma who developed CRS after his 4th cycle of pembrolizumab. His initial presentation was thought to be related to sepsis given his high fevers and hypotension; however, given the lack of improvement despite an extensive workup and broad coverage with antibiotics, CRS was suspected as a potential etiology of his symptoms. Tocilizumab and steroids were successfully used and resulted in the resolution of symptoms without relapse. This case highlights the diagnostic and therapeutic challenges posed by immunotherapy-induced CRS and emphasizes the importance of early recognition to achieve good outcomes.